The impact of diverse performance measurement on the customer-orientated selling behaviours of B2B salespeople - Kerr, Peter (Cranfield University, 2018)
The pervasive use of performance measurement frameworks, such as the balanced scorecard, coupled with the growing complexity of today’s B2B sales role is increasing the need for greater levels of measure diversity to evaluate the performance of the modern salesperson. Yet very little is known regarding the behavioural impacts of using more balanced and diverse measures to evaluate individual salesperson performance. This research investigates the relationship between the use of diverse measures of performance and the customer-oriented selling behavior of B2B salespeople. Based on data collected from 274 business-to-business salespeople from Canada, the United States and the United Kingdom and using partial-least squares, structural equation modelling, the author finds that measure diversity is positively associated with salesperson customer-oriented selling behaviour and that this behaviour is fully mediated through salesperson attitudes towards customer-oriented selling. Findings also suggest that measure diversity within a sales performance measurement system is positively associated with increased levels of supervisory sales coaching activity.
Keywords: Measurement diversity; non-financial measures; sales performance; sales control; attention-based theory; theory of planned behaviour; customer orientation